MAANTAR JUJURAN DALAM KAJIAN DRAMATURGI (STUDI KASUS ADAT PERKAWINAN MASYARAKAT SUKU BANJAR DI KECAMATAN TEMBILAHAN KABUPATEN INDRAGIRI HILIR) - Relanti Yusmita; Mita Rosaliza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Jujuran is a gift from the man to the woman in the form of an agreed amount of money. Jujuran is different from dowry (dowry). Jujuran is not the full property right for the bride as is the bride price. The large amount of jujuran of a woman is influenced by several factors such as the background of the bride, the level of education, employment, and beauty that a woman has. Society considers jujuran as a tradition that has been maintained and must be preserved. The demand for a large amount of jujuran is certainly contrary to the teachings of Islam which makes it easy and does not burden the road to hold a wedding. This research was conducted in Tembilahan District, Indragiri Hilir Regency. The purpose of this study was to determine the practice of